2003
DOI: 10.1002/jcp.10315
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic effects of 17‐β‐estradiol on expression of occludin and transendothelial resistance and paracellular permeability in human vascular endothelial cells

Abstract: Tight junctions govern the paracellular permeability of endothelial and epithelial cells. Aberrations of tight junction function are an early and key event during the vascular spread of cancer and inflammation. This study sought to determine the role of estrogen in the regulation of tight junctions and expression of molecules making tight junctions in endothelial cells. Human endothelial cell, HECV, which express ER-beta but not ER-alpha was used. 17-beta-estradiol induced a concentration- and time-dependent b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
71
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 31 publications
10
71
1
1
Order By: Relevance
“…The Y-box is present in the promoters of genes encoding HER2 and several cell cycle regulators, which operate in a cell density-dependent manner [5,36,37]. Transepithelial resistance and paracellular permeability studies in human vascular endothelial (HUVEC) cell monolayers overexpressing ZO-1 and/or ZONAB demonstrated that the two proteins functionally interact at the HER2 promoter [38], suggesting that they might be part of a signaling system that could regulate epithelial differentiation, proliferation, and paracellular permeability in normal and transformed cells.…”
Section: Discussionmentioning
confidence: 99%
“…The Y-box is present in the promoters of genes encoding HER2 and several cell cycle regulators, which operate in a cell density-dependent manner [5,36,37]. Transepithelial resistance and paracellular permeability studies in human vascular endothelial (HUVEC) cell monolayers overexpressing ZO-1 and/or ZONAB demonstrated that the two proteins functionally interact at the HER2 promoter [38], suggesting that they might be part of a signaling system that could regulate epithelial differentiation, proliferation, and paracellular permeability in normal and transformed cells.…”
Section: Discussionmentioning
confidence: 99%
“…E 2 , 2-ME, and isoflavones enhance endothelial barrier function and reduce its permeability to pro-atherogenic factors such as native and oxidized LDLs (Carbajal & Schaeffer 1998, Delarue et al 1998, Fujimoto et al 1998, Gardner et al 1999, Chi et al 2004, Liu et al 2005, Sumanasekera et al 2007, Dubey & Jackson 2009). The latter effect depends on the modulation of tight junction proteins such as occludin and/or claudin and is mediated via both ERa and ERb (Ye et al 2003, Burek et al 2010, Sandoval & Witt 2011. Furthermore, estrogens promote endothelial cell proliferation and survival.…”
Section: Mechanisms Underlying Anti-atherogenic Effects Of Estrogens mentioning
confidence: 99%
“…Heinrich et al (1999) demonstrated that estrogen promoted a nonadherent phenotype through negative regulation of N-cadherin-mediated cell-cell adhesion by the signaling pathway of estrogen receptor, whereas the treatment of antiestrogen is associated with the presence of adherens junctions. The down-regulation of estrogen receptor induced by estrogen treatment can alter the distribution and constitution of cell junction proteins, such as ZO-1, occludin, claudin-1, E-cadherin, and F-actin, which subsequently disassembles the cell-cell contacts (RothenRutishauser et al, 2002;Ye et al, 2003). Therefore, it is possible that cell junction may be involved in the regulation of the opening area of lymphatic stomata by estrogen.…”
Section: Discussionmentioning
confidence: 99%